Erratum: The Potential of Farmer Field School in Cocoa Extension Delivery:A Ghanaian Case Study - JIAEE Editors (Journal of International Agricultural and Extension Education, 2024)
Correction: The DOI of the article "Okorley, E. L., Adjaro, G., & Bosompem, M. (2014). The Potential of Farmer Field School in Cocoa Extension Delivery:A Ghanaian Case Study. Journal of International Agricultural and Extension Education, 21(2), 32-44” was incorrect as published. The correct DOI is: 10.4148/2831-5960.1230